2018
DOI: 10.1088/1361-6463/aaefe6
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency vibration suppression of a multi-layered elastic metamaterial shaft with discretized scatters

Abstract: With the aim to reduce the total structural weight, this paper presents a novel radial multilayered elastic metamaterial (EM) shaft in which the scattering layer is circumferentially discretized into several arc-shaped sections with rotational symmetry. The dispersion relations and frequency-response-functions (FRF) of a finite structure are determined numerically first with different discretized geometries. To illustrate the mechanisms of band gaps, the eigenmodes were extracted and analyzed together with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The first application of metamaterials, therefore, is to suppress the vibration propagation along the engineering structures based on the band gaps. It is found that the vibration can be attenuated by more than 20 dB in the frequency range of the band gap [80,83,105,107,[118][119] . Due to the remarkable performance of vibration attenuation, metamaterials have been introduced into the vibration isolation floating raft to improve the vibration attenuation and acoustic stealthy performance of underwater vehicles [120] .…”
Section: Potential Applicationsmentioning
confidence: 99%
“…The first application of metamaterials, therefore, is to suppress the vibration propagation along the engineering structures based on the band gaps. It is found that the vibration can be attenuated by more than 20 dB in the frequency range of the band gap [80,83,105,107,[118][119] . Due to the remarkable performance of vibration attenuation, metamaterials have been introduced into the vibration isolation floating raft to improve the vibration attenuation and acoustic stealthy performance of underwater vehicles [120] .…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Li et al 66 designed a six-layer radial metamaterial shaft with arched layers, as shown in Figure 68. They extracted the eigenvalues of the system and determined the frequency response and dispersion curves by using the numerical method.…”
Section: Bandwidth Setting Of Local Resonance Metamaterialsmentioning
confidence: 99%
“…Moreover, passive dampers can involve particles [11,12], periodic sandwich plates [13,14], a honeycomb structure of cells filled with circular carbon tubes forming a composite sandwich structure [15], or a damping layer that can be formed from open-cell foam [16]. The whole structure can be designed as a novel advanced material, e.g., a radial multilayered elastic metamaterial shaft in which the scattering layer is circumferentially discretized into several arc-shaped sections with rotational symmetry [17].…”
Section: Introductionmentioning
confidence: 99%